Physiochemical Characteristics of Soil of a Mixed Shorea Robusta Forest in Rupandehi District, Nepal - Acharya, Rajendra; Shrestha, Bharat Babu (Journal of Natural History Museum, 2015)
Physiochemical characteristics of soil of mixed Shorea robusta forest in Parroha community forest of Rupandehi district (central Nepal) were analyzed. Soil samples were collected from south eastern (SE) and south western (SE) slopes of the forest and analyzed for water holding capacity (WHC), pH, organic matter, nitrogen, phosphorous and potassium. The soil acidic (pH 4.2-6.2) with organic matter 1.87-2.73 %, nitrogen 0.09-0.13 %, phosphorus 4.7-23.3 kg/ha, and potassium 141-191 kg/ha. The SE slope, with high canopy cover and litter content, had relatively better soil characteristics as compared to the SW slope. J. Nat. Hist. Mus. Vol. 26, 2012: 155-162